Gone, but haven't forgotten: insights on plasmapheresis donation from lapsed donors. Issue 3 (23rd September 2020) - Thorpe, Rachel; Nguyen, Lilly; Masser, Barbara M.; Van Dyke, Nina; Davison, Tanya E.
Abstract : Background and Objectives: Blood Collection Agencies in several countries have implemented strategies to increase the number of plasmapheresis collections. Despite this, a sizable minority of plasma donors lapse from donation each year, with little research conducted on this topic. An understanding of the plasma donation experience from the perspective of lapsed donors, insights into why they stopped donating and their views on returning to donate may provide opportunities to intervene to increase the retention and reactivation of plasma donors. Materials and Methods: A qualitative approach was used in this study, with 17 lapsed plasma donors (no plasma donation for at least 13 months) interviewed. A purposive recruitment strategy was used to obtain a sample with diversity in gender (47% men), age (M = 36·2 years, SD = 13·6) and donation experience (M = 9·2 years, SD = 9·6). Semi‐structured, narrative interviews were conducted, with participants describing their plasma donation careers chronologically from first donation to most recent. Results: The majority of participants described at least some aspect of the plasma donation procedure as unpleasant. However, adverse experiences were only attributed to lapsing in a minority of cases, with other participants reporting significant life events, perceived ineligibility and concerns about the safety of the procedure as the reason why they lapsed. Conclusion: It is common for lapsed plasma donors to intend to donate again in the future. Recommendations are given for strategies to address barriers to returning, noting the potential role of tailored education and support.